CURRENT STATE OF FINANCING THE ACTIVITIES OF SCHOOL EDUCATIONAL ORGANIZATIONS IN UZBEKISTAN - Khalilova Shokhsanam Gayrat kizi (American Journals, 2024)
The article examines the opinions of the world's leading scientists on financing the activities of preschool education organizations in Uzbekistan, analyzes the number of children covered by preschool education organizations and the preschool education system during the years 2017–2023, analyzes the main directions and goals of using public-private partnership mechanisms in the field of preschool education, draws justified conclusions and develops proposals for financing the activities of preschool education organizations in Uzbekistan, and gives recommendations for their application in our country.
Keywords: Public-private partnership, privatization, investment climate, preschool education, public assets.